Trichromacy and ultraviolet vision in a nocturnal marsupial - Leah M. Nielsen; Harald Beck; Christopher Oufiero; Robert J. Johnston; Jesse S. Handler; Joanna F. D. Hagen (Scientific Reports)
Abstract Color vision among mammals is diverse and complex, with many physiological and genetic factors affecting spectral sensitivity, the ability to perceive different wavelengths of light. In this study, the color vision of the sugar glider (Petaurus breviceps), a nocturnal, gliding mammal, was examined through a series of behavioral tests, genetic analyses, and immunohistochemistry. This is the first study to classify the color vision capabilities of this species. Sugar gliders demonstrated trichromacy and ultraviolet (UV) sensitivity, the latter of which was further supported by genetic analysis. Visualization of the sugar glider retina exhibited a rod-dominant retina that expresses rhodopsin, short-wavelength sensitive 1 opsin, and long/medium-wavelength sensitive opsin. Diurnal primates were thought to be the only mammals able to visualize trichromatically, however the results of this examination and evidence from a few other marsupial studies provide support for nocturnal trichromacy in Metatheria. Intriguingly, the genetic basis for the medium-wavelength sensitivity in marsupials has yet to be discovered. Our results are evidence of a fourth Australian marsupial that is UV-trichromatic, supporting complex spectral sensitivity and UV vision as benefits to survival in nocturnal environments. Given that Rh1 sensitivity at 501 nm explains the green sensitivity behaviorally, question arises how many other nocturnal ‘dichromatic’ species use rods for trichromatic vision in mesopic light.